Application of the Drill and Practice Method to Improve Arabic Vocabulary Mastery of Students in the Mutawasith Class of Ma'had Lughawy - Hilda Nur Sopia; Siti Sanah; Ade Arip Ardiansyah (Gunung Djati Conference Series, 2025)
The use of non-varied methods in teaching Arabic vocabulary to the students of Ma'had Lughawy has made it difficult for them to understand and master Arabic vocabulary. This research aims to improve the mastery of Arabic vocabulary among the students of Ma'had Lughawy Kelas Mubtadi through the Drill and Practice method. This study employs a classroom action research design with two cycles. Data were collected through observations, tests, and interviews. The results indicate that the Drill and Practice method is effective in improving the mastery of Arabic vocabulary among the students of Ma'had Lughawy Kelas Mubtadi. This is evidenced by the increase in vocabulary test scores, observations showing the students' active participation and enthusiasm, and positive feedback from the students regarding this method.